1991
DOI: 10.1063/1.348695
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering from boron nitride coatings at high temperatures

Abstract: The temperature dependence from ambient to 2325 K of the high frequency E2g mode intrinsic to the hexagonal phase of boron nitride has been determined using a pulsed-excitation gated-detection technique which effectively discriminates against sample blackbody emission. A monotonic decrease of 80 cm−1 in mode frequency accompanied by a marked increase in linewidth was observed over this temperature range. Simultaneous acquisition of both Stokes and anti-Stokes Raman scattering has been demonstrated and provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
25
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 16 publications
8
25
0
Order By: Relevance
“…Figure 6 shows the intrinsic FWHM of the E high 2g mode as a function of temperature determined from the Raman measurements. The rate of FWHM increase with temperature is similar to that reported for a polycrystalline pyrolytic coating [23], but the values of FWHM are consistently ∼1.5 cm −1 below those of Ref. [23], which can be ascribed to the higher crystalline quality of our monocrystalline sample.…”
Section: Line Broadening and Phonon Decay Channelssupporting
confidence: 84%
See 1 more Smart Citation
“…Figure 6 shows the intrinsic FWHM of the E high 2g mode as a function of temperature determined from the Raman measurements. The rate of FWHM increase with temperature is similar to that reported for a polycrystalline pyrolytic coating [23], but the values of FWHM are consistently ∼1.5 cm −1 below those of Ref. [23], which can be ascribed to the higher crystalline quality of our monocrystalline sample.…”
Section: Line Broadening and Phonon Decay Channelssupporting
confidence: 84%
“…Whereas phonon anharmonicities have been studied in detail by means of Raman scattering experiments in the closely related graphite and graphene structures [21,22], no information exists in the literature about phonon anharmonic decay in h-BN. The temperature dependence of the Raman frequency and linewidth of the E high 2g mode was reported for temperatures above RT for a polycrystalline BN coating, and it was concluded that it could not be explained in terms of a simple model involving a single phonon decay channel [23]. Strong coupling of optical phonons to electrons in graphite yields ultrafast electron relaxation via excitation of a hot phonon population, whose lifetime was estimated to be of 7 ps [24].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, thin-film aging effects are mainly caused by absorption of water molecules due to the thin-film microporosity followed by a BN hydrolysis as was pointed out by Hubácek and Ueki. 8 Infrared ͑IR͒ 4,[9][10][11][12][13][14] and Raman spectroscopy, [15][16][17][18][19][20] as well as IR and visible-light ͑VIS͒ spectroscopic ellipsometry ͑SE͒ [21][22][23][24][25] were used to investigate BN thin-film optical and structural properties. It was demonstrated that polarized IR reflection ͑PIRR͒ measurements, 26,27 IR-SE [28][29][30][31][32][33][34] and VIS-SE 25,30 are useful techniques to resolve the BN microstructure from the thin-film optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic modes have symmetry E 1u A 2u and the crystal field gives rise to a splitting between longitudinal (LO) and transverse optical phonons for the other E 1u modes, whereas the E 2g modes remain doubly degenerate each. In Table I we compare our calculations with the experimental data reported for the ÿ point by Raman [14,[21][22][23][24] and infrared [22,25] spectroscopy. The agreement between both data sets is excellent, the largest difference being a 5% underestimate of the A 2u mode, similar to that reported by previous ab initio calculations [12,13].…”
mentioning
confidence: 99%